Pengembangan Perangkat Pembelajaran Terintegrasi Etnomatematika Permainan Congklak Materi Operasi Hitung Pada Peserta Didik Kelas II SD/MI - Fira Febrina; Ahmad Fauzan; Elita Zusti Jamaan; Arnelis Arnelis (Universitas PGRI Madiun, 2022)
Culture is a tradition / habit that exists in society. Basically, culture can be used in learning activities, in addition to making learning more fun, it can also improve student learning outcomes. Learning that involves culture is called Ethnomathematics. Based on this, the researchers are interested in conducting research to develop an integrated learning device for the ethnomathematics of the Congklak game. The objectives of this research are (1) to describe the ethnomathematical elements in the congklak game, (2) to produce an integrated learning device for the ethnomathematics of the congklak game that is valid, practical and effective. This research is a combined research of ethnographic research and development research (Development Research). Ethnographic research data obtained from observations and interviews with cultural experts. The data analysis techniques carried out were: 1) data reduction, 2) data display, and 3) conclusions. The development research was carried out using the Plomp development model. In the Plomp development model there are several phases, namely the initial investigation phase (preliminary research), the development or prototyping phase (development or prototyping phase), and the assessment phase.The results of ethnographic research show that there are ethnomathematics elements in the game of congklak. These elements are grouped into mathematical ideas, namely: counting, locating, playing, and explaining. While development research produces learning tools that are valid, practical, and effective. Learning devices are said to be valid in terms of content and constructs, are said to be practical in terms of implementation, ease and processing time, and are said to be effective in terms of increasing student learning outcomes. Based on the ethnographic and developments that have been carried out, the learning tools in the form of RPP and LKPD are integrated. The ethnomathematics game of Congklak, material for arithmetic operations, is valid, practical, and effective for class II SD/MI students.